Analysis of Salt Marketing Strategy of Local Farmer Groups (Case Study of Labuhan Bontong Village, Tarano District) - Nisa, Nuhidayatun; Anshori, M. Syukron; Kom, M.I. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Labuhan Bontong Village, Tarano Sub-District is one of the largest salt-producing villages in Sumbawa Regency. However, marketing issues such as limited market access, competition with imported salt, and unstable prices continue to hinder the local salt industry in this area. This research aims to determine the marketing strategies carried out by the local farmer group in Labuhan Bontong Village, Tarano Sub-District. The research uses a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The theory used in this research is the Marketing Mix 7P theory. The results of the research show that the marketing strategy of salt by the local farmer group only shows a few strategies such as salt production carried out near the coast and the presence of physical evidence in the form of machine technology that can lift seawater into salt plots, while some do not show any strategies yet, such as pricing that still depends on time/season, promotion still through word of mouth, and the marketing process still uses sacks.